Optimizing a laundering program for textiles in a front-loading washing machine and saving energy. (1st April 2017) - Bao, Wei; Gong, R. Hugh; Ding, Xuemei; Xue, Yue; Li, Pengfei; Fan, Weichao
Abstract: The laundering process has significant environmental impact due to the consumption of energy, water and chemicals. This paper optimized an energy-saving laundering program, especially for shirts or other underwear by efficient experiment design to balance the temperature, main wash time and mechanical action. As a result, energy consumption after optimization is around 1/3 lower than the original, and at the same time, detergency and the rate of fabric abrasion are basically the same as the original. What's more, compared with original program, no additional chemicals or water is used. This finding can help the washing machine manufacturers to optimize washing procedures and it will significantly reduce the environmental impact of washing machines. Highlights: This paper optimized an energy-saving laundering program by efficient experiment design. Apart from energy reduction, the washing efficiency and fabric abrasion are also considered. The amount of water and detergent were kept the same as original, which means no other environmental problem is produced. The laundering program was optimized by balancing the temperature, main wash time and mechanical action.